2001
DOI: 10.1002/rcm.246
|View full text |Cite
|
Sign up to set email alerts
|

Rapid bioanalysis of vancomycin in serum and urine by high‐performance liquid chromatography tandem mass spectrometry using on‐line sample extraction and parallel analytical columns

Abstract: A novel high-performance liquid chromatography tandem mass spectrometry (LC/MS/MS) method is described for the determination of vancomycin in serum and urine. After the addition of internal standard (teicoplanin), serum and urine samples were directly injected onto an HPLC system consisting of an extraction column and dual analytical columns. The columns are plumbed through two switching valves. A six-port valve directs extraction column effluent either to waste or to an analytical column. A ten-port valve sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 20 publications
2
62
0
Order By: Relevance
“…Indeed, several LC-MS/MS methods for the quantification of serum vancomycin concentrations have been described previously [7][8][9]. These methods, however, rely on internal standard compounds with are structurally not related to the target analyze (teicoplanin, atenolol).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several LC-MS/MS methods for the quantification of serum vancomycin concentrations have been described previously [7][8][9]. These methods, however, rely on internal standard compounds with are structurally not related to the target analyze (teicoplanin, atenolol).…”
Section: Introductionmentioning
confidence: 99%
“…Comparing HPLC methods with the immunologic, it is observed that the former presents better accuracy and precision but higher analytical delay and involve pre extraction of the analyte. To avoid the necessity of the pre treatment some HPLC with direct injection, using pre extraction columns, have been suggested 54,66 .…”
Section: Resultsmentioning
confidence: 99%
“…When the HPLC technique is used for the determination of vancomycin in biological fluids, the extraction procedure of the analyte is done based on chemical processes, involving protein precipitation and use of organic solvents. In some methods, however, the extraction process is associated to the chromatography as continuous systems 56,59,66 . Recently analytical techniques, where the samples are injected without treatment, have been developed.…”
Section: Chromatographic Methodsmentioning
confidence: 99%
“…In the clinical laboratory the use of this technique has been efficient for determination of analytes in several biological fluids. Therefore, HPLC has been developed for the analysis of vancomycin in medicines, as well as for the determination in biological fluids 17,24,[26][27][28][29][30][31][32][33][34] . Kitahashi and Furuta 35 developed an assay for measuring vancomycin concentration by micellar electrokinetic capillary chromatography with detection at 210 nm using direct serum injection.…”
Section: Clinical Applicationmentioning
confidence: 99%